EFFECT OF DIFFERENT CLEANING PROTOCOLS ON THE HARDNESS OF FLEXIBLE DENTURE BASE MATERIAL "THERMOSENS” - Rumen Radev; Nikolay Apostolov; Elka Radeva (Journal of IMAB)
Introduction. The growing use of flexible dentures in everyday dental practice calls for further studies on how various disinfection methods influence their mechanical properties, particularly their hardness. Purpose. The aim of the study was to evaluate how different cleaning techniques under varying conditions affect the hardness (HVN) of the "ThermoSens" denture base material. Materials and Methods. Forty flexible denture samples, measuring 10 mm in width and 3 mm in height, were made and grouped into ten sets (T1-T10) based on the disinfection method applied. For 30 days, all samples were submerged in artificial saliva and cleaned with common products (soap, toothpaste, Protefix, and Corega tablets). Each sample was then evaluated in five surface areas using the Vickers hardness test, with the data statistically analyzed using IBM SPSS Statistics 26, Excel 2015, and EdrawMax 7. Results. No statistically significant difference was found between the individual groups using different disinfection methods and protocols compared to the control group. Only in group 2, daily cleaning with Corega tablets (9.3 HVN) resulted in a statistically significant increase in hardness compared to the control group.When comparing experimental group 2 with the other groups, a statistically significant difference was found with all groups except group 3 (9.0 HVN) and group 4 (9.1 HVN). Groups 2, 3, and 4 exhibited the highest hardness. Conclusion. The use of different conventional cleaning methods does not alter the hardness of the flexible ThermoSens denture base material.